IMPLEMENTASI UNDANG-UNDANG NOMOR 25 TAHUN 2009 TENTANG PELAYANAN PUBLIK TERHADAP PELAYANAN KHUSUS DI KECAMATAN ALANG-ALANG LEBAR KOTA PALEMBANG (STUDI KASUS PASAL 29) - Antartila, Antartila (Jurnal Ilmiah Administrasi Dan Sosial, 2022)
The research was conducted regarding the Implementation of Law Number 25 of 2009 concerning Public Services for Special Services in Alang-Alang Lebar District, Palembang City (Case Study of Article 29). The research used in this study uses qualitative methods. Data collected through observation, interviews, and documentation. Data analysis techniques are carried out by data reduction, data presentation and drawing conclusions. Based on the analysis of the research conducted by the author regarding the Implementation of Law Number 25 of 2009 Article 29 at the Alang-Alang Lebar Office in Palembang City, that implementation at the Alang-Alang Lebar Village Office in Palembang City has been carried out properly and according to regulations although there are still some deficiencies . in implementing this policy, the Implementation of Law Number 25 of 2009 concerning Public Services for Special Services at the Alang-Alang Lebar District Office of Palembang City, is in accordance with policy standards and objectives, resources, characteristics of implementing agents, inter-organizational communication, social conditions , economics and politics and the disposition of the attitudes of the executors. But at the Alang-Alang Lebar District office, Palembang City, which is contained in the Disposition of the Implementor, there is still a slight deficiency, namely that the employees there are still lacking in providing aspirations, needs or hopes for people with special needs.